Reconstructing the Philosophy of Science in the Project-Based Eco-Citizenship Learning Model for Elementary Education: A Systematic Literature Review - Chairan Zibar L.Parisu; Insih Wilujeng; Woro Sri Hastuti; Arna Juwairiyah (CV. Gerasi Insan Nusantara, 2026)
This study aims to examine the reconstruction of the philosophy of science in the Project-Based Eco-Citizenship learning model in elementary education through a Systematic Literature Review (SLR) approach. This study examines 30 selected articles from the Google Scholar, Scopus, and SINTA databases published in 2015–2025. The analysis was conducted using the PRISMA stages and thematic analysis examined from the perspective of the philosophy of science, namely ontological, epistemological, and axiological dimensions. The results of the study indicate that ontologically, students are positioned as active subjects who learn through direct interaction with the environment as the real reality of learning. Epistemologically, knowledge is built through experience, collaboration, and reflection in contextual project activities so that learning becomes more meaningful and applicable. Meanwhile, axiologically, this model plays a role in instilling the values of environmental concern, social responsibility, and sustainability that shape the character of eco-citizens in students. The integration of these three dimensions shows that Project-Based Eco-Citizenship is not only oriented towards cognitive achievement, but also character development and ecological awareness. Thus, this model is relevant to the demands of the Independent Curriculum and the strengthening of 21st-century skills in forming a generation that is critical, collaborative, creative, and cares about the environment.